Socio-economic security of Russia: status and prospects - S. A. Dyakov; K. E. Shamray (Вестник Северо-Кавказского федерального университета)
Introduction. Under the conditions of sanctions pressure and Western European isolation, Russian economy is at the stage of structural transformation, determined by restructuring of the labor market, changes in the functioning of various industries, and the reorientation of consumer demand. This modification of the domestic economy is subject to a whole range of external and internal challenges and threats to the socio-economic security of the state. Goal. The purpose of the study is a detailed analysis of the state of socio-economic security in Russia, identifying the most priority mechanisms for its development. Materials and methods. The methodological basis of the research is analysis, comparison and generalization. The materials of the scientific work are based on Rosstat statistics, publications of economic scientists, and online resources. Results and discussion. The attributive characteristics of Russia as a welfare state are presented. The main indicators of the socio-economic security of the country are considered. The state of the labor market in Russia, the standard and quality of life of citizens are analyzed. A retrospective analysis of the level of poverty in the Russian Federation has been carried out, and the main causes have been revealed. A regression analysis was compiled, the poverty level acted as an effective indicator, the factorial signs were the levels of inflation and unemployment, the average nominal wage, and the cost of living. Proposals for qualitative improvement of socio-economic security of Russia are specified. Conclusion. The sanctions pressure has introduced new requirements, rules and regulations according to which the domestic economy should develop and function. Russia has sufficient financial, labor, and natural resources for the intensive development of socio-economic security.